Notes from Quebec: PRIVATE EDUCATION IN QUEBEC: PROPOSED LEGISLATION and THE TASK FORCE ON ENGLISH EDUCATION - Burgess, Donald (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1992)
PRIVATE EDUCATION IN QUEBEC: PROPOSED LEGISLATION The Quebec Government has recently introduced legislation concerning the regulation of private education (Bill 141). The major elements of the legislation are examined and compared to the current Private Education Act. Initial responses suggest that the legislation is controversial and that it will be either drastically amended or withdrawn. RÉSUMÉ Le gouvernement du Québec a récemment déposé un projet de loi portant sur la réglementation de l'enseignement privé (projet de loi 141). Les principaux éléments de ce projet sont analysés et comparés aux dispositions de l'actuelle Loi de l'enseignement privé. Les premières réactions révèlent que le projet de loi est controversé et qu'il sera considérablement modifié ou abandonné. THE TASK FORCE ON ENGLISH EDUCATION ABSTRACT ln 1991 the Quebec Minister of Education established a Task Force to inquire into several matters affecting the English-language school system, including severely declining enrolments. The Task Force has recommended changes to the law concerning accessibility to English schooling, to the organization of the Ministry of Education, to school board structures, and to the curriculum. It remains to be seen which of these recommendations will be implemented. RÉSUMÉ En 1991, le ministre québécois de l'Éducation a créé un groupe de travail chargé d'étudier plusieurs problèmes qui affectent le réseau scolaire anglophone, notamment la diminution marquée des effectifs étudiants. Le groupe de travail a recommandé que des modifications soient apportées à la loi en ce qui a trait à l'accès à l'école anglaise, à l'organisation du ministère de l'Éducation, à la structure des commissions scolaires et aux programmes d'études. Il reste à voir si ces recommandations seront suivies d'effets.